Free But Fantastic: The Paradox of Jateng Fair 2025's Strategy in Creating a Sustainable Tourism Ecosystem - Nurul Farida, Dita Aulia Rachma; Kristanto, Heri; Mistriani, Nina (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
FREE BUT FANTASTIC: THE PARADOX OF JATENG FAIR 2025'S STRATEGY IN CREATING A SUSTAINABLE TOURISM ECOSYSTEM Dita Aulia Rachma Nurul Farida1*, Heri Kristanto2, Nina Mistriani31Hospitality & Tourism Department, Politeknik Nest Sukoharjo, Indonesia2Hospitality & Tourism Department, Politeknik Nest Sukoharjo, Indonesia3Tourism Management Department, Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, Indonesia